Fine and Gross Motor Skill Proficiency Differences of Children Aged 8-9 Years based on Gender - Wibowo, Ricky; Budiman, Didin; Sumarno, Gano (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
The aim of this study was to investigate the differences of proficiency in fine motor skills and gross motor skills based on gender. 147 children at the elementary school level were divided into two groups according to their gender. 78 Boys (aged 8.5±0.4) and 69 girls (aged 8.3±0.3) have participated in this study. The instrument used in this research was the Movement Assessment Battery for Children–second edition (MABC-2). The statistical test used a non-parametric Mann-Whitney U test, while r coefficient was used to interpret the effect size. The result of the study showed that the manual agility of boys was better than girls. However, the difference was not significant and the effect size was small (p .05, r = .004). The result also showed that the catching and throwing skills of boys were better. The difference was not significant and the effect size was small (p .05, r = .023). Meanwhile, the balance of the boys was better than the girls with a significant difference and medium effect size (p .05, r = .055). In general, the result of the study shows that boys are better than girls in fine and gross motor skills proficiency.